2021
DOI: 10.32920/ryerson.14657571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Framing international crises: a comparative content analysis of media texts on the collapse of Venezuela

Abstract: This research explores mainstream and diasporic media coverage and discourses surrounding the Venezuelan economic and political crisis from late March 2017 until early May 2018. A comparative content analysis was applied to a total of 256 news articles, editorials, and stories from the Toronto Star, one of Canada’s largest newspapers, and from La Portada Canadá, a Spanish-language Latin American newspaper in Toronto. The results demonstrated diasporic media’s appropriation of journalistic biases such as human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…While, for example, there are Spanishlanguage newspapers available in the Toronto region (such as La Portada, a Latin American newspaper in the GTA made by and for Spanish-speaking immigrants and people in the area) as well as an Arabic-language newspaper (Arab Toronto Newspaper), the Toronto-based, English-language papers were chosen in order to better represent the way that Canadians portray and perceive refugees. Olinto (2018) conducted a comparison of the Toronto Star and La Portada and found that a limitation to the study was that the papers were written in different languages and that "these language differences affect the way in which both newspapers have defined and illustrated" (p. 24) the crisis. Furthermore, the newspapers of study contained articles with discourses on both the local level as well as the national level.…”
Section: 1: Introductionmentioning
confidence: 99%
“…While, for example, there are Spanishlanguage newspapers available in the Toronto region (such as La Portada, a Latin American newspaper in the GTA made by and for Spanish-speaking immigrants and people in the area) as well as an Arabic-language newspaper (Arab Toronto Newspaper), the Toronto-based, English-language papers were chosen in order to better represent the way that Canadians portray and perceive refugees. Olinto (2018) conducted a comparison of the Toronto Star and La Portada and found that a limitation to the study was that the papers were written in different languages and that "these language differences affect the way in which both newspapers have defined and illustrated" (p. 24) the crisis. Furthermore, the newspapers of study contained articles with discourses on both the local level as well as the national level.…”
Section: 1: Introductionmentioning
confidence: 99%